Peran Etika Advokat dalam Penyelesaian Sengketa Manipulasi Data Pada Hukum Keluarga Islam - Fathurrozi, Adi (Jurnal Ilmiah Global Education, 2025)
Data manipulation disputes in Islamic family law, such as falsification of marriage documents, manipulation of marriage age, and fabrication of evidence, are complex and sensitive issues. In the process of resolving them, advocates play an important role as law enforcers and mediators who must uphold professional ethics. This study aims to analyze the role of advocate ethics in dealing with and resolving data manipulation disputes in Islamic family law with a normative legal approach. The research method uses a literature study of laws and regulations, advocate codes of ethics, and Islamic family law and professional ethics literature. The results of the study indicate that the application of ethical values ​​of the advocate profession, such as integrity, honesty, and social responsibility, is crucial in maintaining justice and legal certainty in these disputes. In addition, legal ideals that prioritize substantive justice and social benefits must be the main foundation in advocacy practices in the field of Islamic family law. This study recommends strengthening advocate professional ethics education and updating regulations that more specifically regulate the resolution of data manipulation disputes in Islamic family law so that the legal process runs fairly and with dignity.